Building Strategic Workforce Reserve and Other Tasks of Modern Education - Matraeva, Liliia V.; Konov, Alexey A.; Bashina, Olga E.; Mamaeva, Natalia V. (International Review of Management and Marketing, 2016)
In the article terms workforce and workforce potential are analyzed in depth aiming to show different viewpoints on this issue. Detailed analysis allows authors to arrive at definition that “workforce potential” is a complex multilayer composition of individual skills specific for an individual worker, includes professional knowledge and cognitive capabilities and that development of this category is heavily dependent on motivation and expertise. Taking into consideration the speed with which changes are happening nowadays authors are pointing that intellectual skills are the only resource that allows to cope with the speed with which new knowledge is created nowadays. That’s why one of the crucial ways to develop workforce potential is to advance its “intellectualization” – intellectual skills and modern education is supposed to solve this task. The main goals of society and state in creating strategic workforce potential consist in long-term educational goals and strategy setting the way that take in consideration the ever accelerating pace of technologic lifestyle, forecasts and foresights in economy, social life, basic sciences and technologies; uniform national approach to motivation; higher education and corresponding additional courses modification in terms of both form and content. Keywords: workforce, intellectual skills, motivation, workforce potential JEL Classifications: J21, J23, J24